Aspects of the sentencing process in child sexual abuse cases - Van der Merwe, Annette (Rhodes University, Faculty of Law, Law, 2006)
This thesis investigates current sentencing practices relating to the diverse, complex and emotionally laden phenomenon of child sexual abuse. It focuses on relevant legislative provisions, on case law and on an empirical study conducted amongst regional court magistrates. Trends, developments and problems are analysed and possible solutions to the main problems identified are investigated. The thesis concludes with proposed guidelines regarding the sentencing process in child sexual abuse cases. Such guidelines address general and specific principles, the use of victim impact statements, the increased recognition and use of behavioural science in the sentencing phase with regard to both the victim and the offender, and relevant aggravating and mitigating factors. The guidelines are an attempt to give some structure to the current haphazard approach adopted by the courts with regard to harm experienced by the victim. They are also aimed at assisting experts to provide more effective and reliable pre-sentence reports. Further, the thesis attempts to provide clarity concerning the factors that are considered to be aggravating or mitigating in the offence category, child sexual abuse, as well as with regard to the weight that should be attached to them. In addition, recommendations are made for the purpose of possible law reform and further research in relation to the regulation of judicial discretion through the introduction of formal sentencing guidelines, victim impact statements and the accommodation of behavioural science in the sentencing process pertaining to sexual offenders. This proposal is based on current South African sentencing practices as reflected in the consolidation of local judgments scattered over many years in different law reports and, to some extent, on English, Canadian, Australian and American sentencing practices as researched in this study.
Keywords: Child sexual abuse -- South Africa; Sexually abused children -- Legal status, laws, etc -- South Africa; Child abuse -- Law and legislation -- South Africa; Sex crimes -- South Africa; Sentences(Criminal procedure) -- South Africa